PENGARUH KEMAMPUAN PEMBELAJARAN ORGANISASI TERHADAP KOMPETENSI, TINGKAT DIVERSIFIKASI DAN KINERJA STAI SWASTA DI WILAYAH III CIREBON - Asep Kurniawan (LP2M IAIN Syekh Nurjati Cirebon, 2012)
Management of STAIS in Cirebon Region III should be flexible, fast,innovative, and integrated with creative human resources. Therefore, Islamic private colleges are required to be able to adapt, develop and conduct learning through learning organization (Kogut and Zander, 1992; Henderson and Cockburn 1994). This study aimed to verify and analyze the influence of learning organization capabilities on competencies, level of diversification, and performance of Islamic private college in Cirebon Region III West Java. In order to achieve and maintain competitive advantages in a business environment that changes rapidly, the organizations must be able to increase their capacities of learning (Marquardt, 1996:15). This study used quantitative methods. Research respondents were all management team of 6 STAIS in Region III Cirebon. Respondents totaled 134 people consist of 31 leaders as population, 59 employees, and 41 lecturers as samples. Research instrument was a questionnaire. Data analysis technique was Structural Equation Modeling (SEM) with the AMOS (Analysis of Moment Structure) version 5 and SPSS version 15.0. The study results showed that there were significant influences of learning organization capability on competence of Islamic private colleges. Therefore, the research hypothesis one (H1) which stated that the ability of learning organization of STAIS effect significantly on the competences STAIS were accepted. The positive direction indicated that the increased ability of learning organization conducted by STAIS in Cirebon Region III will cause it able to increase its competences. Based on the important findings of this study, then to improve its performance, it is advisable to STAIS to improve the competence of lecturers a valuable, rare, difficult to imitate and hard to replace and increase diversification through a number of courses and interrelated courses.